Factors Causing Land Boundary Disputes in Bekasi City and Efforts to Resolve Them: Faktor Penyebab Sengketa Batas Tanah di Kota Bekasi dan Upaya Penyelesaiannya - Rifki, Muhammad Aditya; Suhadi, Suhadi (Faculty of Law, Universitas Negeri Semarang, 2024)
Land boundary disputes, often caused by natural factors and competition among two or more individuals over land ownership, indicate tension in human interactions, and the sought-after resolution is an effort to improve relationships. One common approach is through the judiciary, but there is also an alternative to resolving disputes through peace, known as mediation, which can be facilitated by entities such as the Land Office of Bekasi City. The author discusses this topic to explore how mediation by the Land Office can be used in settling land boundary disputes, based on the author's observations at the Land Office of Bekasi City and the chronology of related cases. From the above description, the author uses a Qualitative approach with the Empirical Juridical method aimed at identifying the causes of land boundary disputes at the Land Office of Bekasi City and the resolution of land boundary disputes between applicants and respondents at the Land Office of Bekasi City. The research highlights the public's lack of understanding of land preservation and registration as the main trigger for land boundary disputes. Insufficient awareness in placing land markers has the potential to cause conflicts, resulting in a violation of the principle of contradiction. To reduce the possibility of disputes, landowners need to complete the registration process with accurate measurements, involving land surveyors and witnesses. The Land Office of Bekasi City offers a solution through mediation, with three mediation summons to facilitate an amicable resolution. It is crucial for landowners to officially register their land at the land office, gather ownership evidence, and conduct re-measurements and stake installations to maintain legal certainty.